Systematic Literature Review: Ekplorasi Etnomatematika Pada Rumah Adat di Indonesia - Yustinaningrum, Bettri (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2024)
Indonesia has various cultural diversity, one of which is traditional houses. Each region has traditional houses that have their own style. The aim of this research is to explore the ethnomathematics found in traditional houses through literature studies from previous research. The research method applied is a systematic literature review. The search for journals and proceedings used the Google Scholar database via publish or perish, with a time span from 2019 to 2023. Based on the search results using publish or perish, 220 articles were obtained. The articles were then selected based on exclusion and inclusion criteria to become 22. The results of the analysis showed that the concept of mathematics is often found in home ornaments and architecture. Mathematical concepts discovered include flat shapes, spatial shapes, transformation geometry, similarity, and congruence. Mathematical concepts found in traditional houses can be implemented into learning by using them as questions, learning activities, learning media, and learning resources.